Cognitive Phenomena of Style and Creativity - Chiu Shui Chan (DEPARCH Journal of Design Planning and Aesthetics Research)
This paper explains a cognitive notion of style and creativity approached from reviewing the general concepts of design thinking and cognition, exploring patterns of cognitive operations conducted in the design processes, elaborating how style and creativity are coming from executing these cognitive operations. In fact, style and creativity are the resulting phenomena, or byproducts, coming from design cognition. Thus, based on the concept of resulting phenomena from cognition as the premise, this paper itemized the theories of “changing or modifying our ways of executing our design cognition, our style and creativity would be improved.” Especially, style and creativity, as defined by features appearing in design products, should be treated as physical entities that they could be identified, recognized, and measured instead of abstract notions of intangible elements. Finally, the correlations between style and creativity are summarized to conclude the impact of design cognition. Hopefully, this paper will provide an outline for the ways to improve our style and creativity in design.